Manifestation of historical empathy by Uzbek people - Muminov, Alisher G.; Muminov, Otabek U. (Journal of the Belarusian State University. History, 2025)
The content of the concept «empathy» is revealed. The peculiarities of its manifestation by Uzbek people in different periods of history are considered. It is pointed out that the population of the Turkestan region showed empathy, kindness, tolerance, mercy and generosity towards the peoples who moved to this territory after its conquest by the Russian Empire. Much attention is paid to the period of the World War II when Uzbekistan became a second homeland for many people evacuated from front-line regions. The behaviour of the peoples of the USSR during the Tashkent earthquake is described.